2019
DOI: 10.1021/acschembio.9b00663
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Regorafenib-Induced Toxicity through Inhibition of Gut Microbial β-Glucuronidases

Abstract: Regorafenib (Stivarga) is an oral small molecule kinase inhibitor used to treat metastatic colorectal cancer, hepatocellular carcinomas, and gastrointestinal stromal tumors. Diarrhea is one of the most frequently observed adverse reactions associated with regorafenib. This toxicity may arise from the reactivation of the inactive regorafenib-glucuronide to regorafenib by gut microbial βglucuronidase (GUS) enzymes in the gastrointestinal tract. We sought to unravel the molecular basis of regorafenib-glucuronide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…However, no systematic characterization of microbial enzymes that process particular classes of medications or a list of medications that are metabolized by such enzymes were presented. For example, the β-glucuronidase activity has been reported to cause severe toxicity for several medications (such as irinotecan [ 10 , 11 , 58 ], diclofenac [ 59 ], mycophenolate mofetil [ 60 ], and regorafenib [ 61 ]) and it has been demonstrated that this toxicity can be reduced by co-administration of β-glucuronidase inhibitors [ 59 , 61 ]. However, one may wonder if there are other drugs that could be affected by β-glucuronidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no systematic characterization of microbial enzymes that process particular classes of medications or a list of medications that are metabolized by such enzymes were presented. For example, the β-glucuronidase activity has been reported to cause severe toxicity for several medications (such as irinotecan [ 10 , 11 , 58 ], diclofenac [ 59 ], mycophenolate mofetil [ 60 ], and regorafenib [ 61 ]) and it has been demonstrated that this toxicity can be reduced by co-administration of β-glucuronidase inhibitors [ 59 , 61 ]. However, one may wonder if there are other drugs that could be affected by β-glucuronidase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to all previously mentioned drugs, several others listed in S1 Data were reported to be affected by β-glucuronidase, including irinotecan [ 11 , 78 , 79 ], regorafenib [ 61 ], tamoxifen [ 80 ], mitiglinide [ 81 ], clozapine [ 82 ], and zidovudine [ 83 ]. In summary, among the 100 drugs that we predicted to be metabolized by β-glucuronidases, we compiled evidence supporting the prediction for over 20 of them.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the risks associated with REG therapy may be increased by other underlying factors, including prior oncologic and non-oncologic therapies, concomitant medications and other comorbidities. 43 46 …”
Section: Discussionmentioning
confidence: 99%
“…Regorafenib is a multikinase inhibitor with excellent antitumor effects. Microbial reactivation of regorafenib-glucuronide in the gastrointestinal tract by β -glucuronidases is the major cause of gastrointestinal toxicity 164 . Similar to that of CPT-11 and diclofenac, inhibition of microbial β -glucuronidases is believed to reduce regorafenib-induced toxicity 164 .…”
Section: Gut Microbiota-oriented Precision Medicinementioning
confidence: 99%
“…Microbial reactivation of regorafenib-glucuronide in the gastrointestinal tract by β -glucuronidases is the major cause of gastrointestinal toxicity 164 . Similar to that of CPT-11 and diclofenac, inhibition of microbial β -glucuronidases is believed to reduce regorafenib-induced toxicity 164 . These studies suggested the possibility of the combinational use of bacterial β -glucuronidases for reducing the toxicity of drugs; however, additional clinical studies should be carried out to prove the feasibility of this approach.…”
Section: Gut Microbiota-oriented Precision Medicinementioning
confidence: 99%